Contextualizing The Role Of Commissive Illocutionary Acts In Goodfellas Movie - Manuaba, Ida Bagus Dananjaya Andika; Indriani, Ketut Santi; Krisnawati, Ni Luh Putu (International Journal of Linguistics and Discourse Analytics, 2025)
This research investigates the functions of commissive illocutionary acts in Goodfellas (1990), with the aims of identifying their types and examining their contextual meanings. The study focuses on character dialogues containing commissive intent, specifically promises, threats, offers, refusals, and swears. The data consist of selected character utterances systematically documented from the film script and scenes through careful note-taking, and they are analyzed using a qualitative descriptive approach. Speech act classification is based on Searle et al.’s (1985) framework, while contextual meaning is interpreted using Holmes’s (2013) sociolinguistic model of social dimensions, which accounts for factors such as social distance, relative power, and formality. The integration of sociolinguistic perspectives in pragmatic analysis has been widely recognized as essential for understanding language use in socially embedded contexts (Laba & Wijayanti, 2022; Laba & Narlianti, 2025). A total of five commissive utterances were analyzed, each shaped by distinct contextual and interpersonal factors. The findings show that integrating Holmes’s sociolinguistic model provides a deeper understanding of how commissive acts are realized in film discourse, thereby contributing to the study of speech acts in cinematic communication.